Changing friction at the base of an Alpine glacier - Gräff, Dominik; Walter, Fabian (Scientific reports, 2021)
Repeating earthquakes are a global phenomenon of tectonic faults. Multiple ruptures on the same fault asperities lead to nearly identical waveforms characteristic for these seismic events. We identify their microseismic counterparts beneath an Alpine glacier, where basal sliding accounts for a significant amount of ice flow. In contrast to tectonic faults, Alpine glacier beds are subject to large variations in sliding velocity and effective normal stresses. This leads to inter- and sub-seasonal variations in released seismic moment from stick–slip asperities, which we explain with the rate-and-state friction formalism. During summer, numerically modelled effective normal stresses at asperities are three times higher than in winter, which increases the local shear resistance by the same factor. Stronger summer asperities therefore tend to form in bed regions well connected to the efficient subglacial drainage system. Moreover, asperities organise themselves into a state of subcriticality, transferring stresses between each other. We argue that this seismic stick–slip behavior has potentially far-reaching consequences for glacier sliding and in particular for catastrophic failure of unstable ice masses.